Sink or swim - Mlynowski, Sarah (New York, N.Y. : Scholastic Press, 2013)
Once again Abby and her brother Jonah go through the magic mirror in their basement, and this time they find themselves interfering in the Little Mermaid story--and needing to set things right and make sure everyone has a happy ending.
Keywords: Fairy tales; Characters in literature -- Fiction; Magic mirrors -- Juvenile fiction; Mermaids -- Juvenile fiction; Brothers and sisters -- Juvenile fiction